Beyond the Boundaries of Faith: A Multidimensional of Religious Spatial Segregation in the Context of Urban Society - Hasaniy, Nur Rif'ah; Azisurrohman, Abdul (Yayasan Irwan Abdullah Cendekia, 2024)
This study aims to analyzes the spatial dimension of religion contributes to polarization and conflict between religious groups in urban societies. Using a qualitative descriptive approach and literature review method, this research explores the forms, impacts, and prevention efforts of religious spatial segregation through analysis of cases involving the dissolution of religious rituals and rejection of houses of worship construction. This study argues that the spatial dimension of religion reinforces the boundaries of religious differences, transforming them from imaginary to clear and practical boundaries, thus giving rise to tensions between religious groups. In order to address religious violence resulting from segregation, this study proposes a peacebuilding design with an integrative structural and socio-cultural approach. The research findings indicate that the concept of religious spatiality is both ambiguous and paradoxical, with blurred categorizations of space trigger contestation of meaning between groups, potentially leading to conflict and violations of religious freedom. This study contributes to a more comprehensive understanding of the dynamics of religious conflict in urban contexts and highlights the importance of a spatial approach in conflict resolution and peacebuilding efforts.